2020
DOI: 10.1177/1538574420923815
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Carotid Restenosis Using Transcarotid Revascularization

Abstract: Objective: Transcarotid artery revascularization (TCAR) using the ENROUTE Neuroprotection System (Silk Road Medical) is a United States Food and Drug Administration–approved treatment modality for stroke risk reduction in the setting of carotid artery stenosis. The goal of this investigation was to define the real-world outcomes associated with the application of this technique to patients presenting with restenosis after previous carotid endarterectomy (CEA) or transfemoral carotid artery stenting (TF-CAS). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…35 TCAR has also been preliminarily proved to be safe in the treatment of carotid artery restenosis and carotid artery aneurysm. 36,37 At present, TCAR provides a new option for the restenosis treatment after CEA and TFCAS. 38 Also, two case reports have demonstrated that TCAR could be used to treat carotid artery pseudoaneurysm and outcomes were satisfying.…”
Section: Discussionmentioning
confidence: 99%
“…35 TCAR has also been preliminarily proved to be safe in the treatment of carotid artery restenosis and carotid artery aneurysm. 36,37 At present, TCAR provides a new option for the restenosis treatment after CEA and TFCAS. 38 Also, two case reports have demonstrated that TCAR could be used to treat carotid artery pseudoaneurysm and outcomes were satisfying.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Multiple national studies have also demonstrated the safety and efficacy of TCAR in high-risk patients, irrespective of age, symptomatic status, contralateral carotid occlusions, and restenotic lesions. [18][19][20][21][22][23][24] Although the clinical benefits of TCAR have been clearly established, there is a paucity of literature comparing its cost-effectiveness with that of CEA. This is particularly pertinent as health care costs currently represent 18% of U.S.…”
mentioning
confidence: 99%
“…[16][17][18][19][20] However, for the treatment of restenosis after CEA, a review of the literature reveals a single, promising multi-institutional experience of 55 patients receiving TCAR with no comparison arms. 21 The aim of this study is to use real-world national data from the vascular quality initiative (VQI) to compare the outcomes of TCAR, TFCAS, and redo-CEA in patients undergoing treatment for restenosis after CEA.…”
mentioning
confidence: 99%